Particles containing silicon and lithium

JP7629398B2Active Publication Date: 2025-02-13ALBEMARLE CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021519561
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-10-12
Filing Date
2019-10-11
Publication Date
2025-02-13
Estimated Expiration
2039-10-11

AI Technical Summary

Benefits of technology

【0049】 本発明の利点の1つは、加熱工程を通常不活性雰囲気下で行う必要がないことである。しかしながら、不活性雰囲気下で加熱工程を行うことが好ましい。不活性雰囲気は、静的なものであっても不活性ガス(複数可)の流れであってもよい。本明細書を通して使用される「不活性雰囲気」は、本質的に酸素を含まない気体または気体混合物を指し、偶発的な量の酸素が不活性雰囲気中に存在していてもよい。本発明の実施においては、リチウム金属及び/またはリチウム合金が使用されない限り、不活性雰囲気中に水が存在することができる。不活性雰囲気は、通常はアルゴン、窒素、ヘリウムであり;2種以上の不活性ガスの混合物が使用されてもよく;窒素及びアルゴンが好ましい。リチウム前駆体がリチウム金属及び/または1種以上のリチウム合金を含む場合には、不活性ガスは好ましくはアルゴンである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629398000006
    Figure 0007629398000006
  • Figure 0007629398000007
    Figure 0007629398000007
  • Figure 0007629398000001
    Figure 0007629398000001
Patent Text Reader

Abstract

The present invention provides compositions comprising coated silicon-containing particles, the coating of which comprises carbon and one or more lithium silicates, the coated silicon-containing particles having a carbon content of about 0.10 wt.% or greater and a lithium content of about 1 wt.% or greater, based on the total weight of the coated particles. Methods for preparing these compositions are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to particles containing silicon and / or silicon oxide coated with a layer comprising carbon and lithium silicate. [Background technology]

[0002] Silicon oxides are often used in lithium-ion batteries as anode (negative) active materials to improve the energy density of the battery. In the first cycle of a lithium-ion battery, the irreversible loss of active lithium is believed to be due to the side reaction of silicon oxides with lithium to form lithium silicate, which is an irreversible loss of some lithium from the cathode and electrolyte.

[0003] In order to suppress the irreversible reaction of forming lithium compounds that do not contribute to charging and discharging and to improve the initial charge and discharge efficiency, lithium doping of silicon oxide to form lithium silicate in silicon oxide has been considered. Known methods for lithium doping of silicon oxide usually include two steps and often require an inert atmosphere. Summary of the Invention

[0004] The present invention provides a silicon-containing particle having a coating comprising carbon and lithium silicate, the silicon-containing particle being typically a silicon particle and / or a particle comprising one or more silicon oxides, or a mixture of silicon particles and particles comprising one or more silicon oxides. The particles comprising one or more silicon oxides often contain some elemental silicon; the silicon particles often contain a small amount of one or more silicon oxides. Advantageously, the coating can be formed on the particle in one step, and the coating is believed to be substantially uniform.

[0005] An embodiment of the present invention is a composition comprising coated silicon-containing particles, the coating being comprised of carbon and one or more lithium silicates. The coated silicon-containing particles have a carbon content of about 0.10 wt.% or more and a lithium content of about 1 wt.% or more based on the total weight of the coated silicon-containing particles.

[0006] Another embodiment of the present invention is a method for forming a composition comprising silicon-containing particles, the composition comprising a coating thereon, the coating being made of carbon and one or more lithium silicates.The coated silicon-containing particles have a carbon content of about 0.10% by weight or more and a lithium content of about 1% by weight or more, based on the total weight of the coated silicon-containing particles.The method includes mixing together silicon-containing particles and a precursor mixture comprising a liquid medium, a carbon precursor, and a lithium precursor to form a wet mixture, and heating at least a portion of the wet mixture to form a coating on the silicon-containing particles.

[0007] These and other embodiments and features of the present invention will become further apparent from the following description, drawings, and appended claims. [Brief description of the drawings]

[0008] [Figure 1] 1 is a powder XRD pattern of the coated silicon-containing particles prepared as in Example 1. [Diagram 2] 1 is a powder XRD pattern of the coated silicon-containing particles prepared as in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The word "layer" as used throughout this specification has the same meaning as the word "coating". The terms "layer" and "coating" as used with respect to silicon-containing particles indicate that at least a portion of the surface of such particles, preferably substantially all or all of the surface of such particles, is covered or in contact with a "layer" or "coating". Similarly, the term "coated" with respect to silicon-containing particles indicates that at least a portion of the surface of the particle, preferably substantially all or all of the surface of the particle, is covered or in contact with a material that is said to "coat" the particle. Also, the phrase "coated particle" is used interchangeably with the phrase "coated silicon-containing particle" throughout this specification.

[0010] The compositions of the invention are believed to have a core-shell structure, where the shell is a coating or layer containing carbon and lithium silicate, and the core is typically amorphous silicon and / or silicon oxide, which may be referred to as bulk silicon or bulk silicon oxide, respectively.

[0011] The phrase "silicon oxide particles" is used interchangeably with the phrase "particles of one or more silicon oxides" throughout this specification.

[0012] The composition of the present invention is a coated silicon-containing particle having an average particle size of about 0.005 microns or more, preferably about 0.05 microns or more. Usually, the coated particle has an average particle size of about 0.05 microns to about 25 microns; preferably, the average particle size is about 0.1 microns to about 20 microns, more preferably about 0.1 microns to about 15 microns, and even more preferably about 1 micron to about 15 microns.

[0013] The coated particles are silicon-containing particles, which consist of silicon and / or one or more silicon oxides. When the particles consist of silicon, they typically contain about 95% or more silicon, ignoring impurities, and preferably about 99% or more silicon. Since silicon particles often contain small amounts of one or more silicon oxides, impurities are defined here as elements other than silicon and oxygen.

[0014] When the coated particles consist of one or more silicon oxides, the silicon oxides in the coated particles have the general formula SiO x and x is about 0.75 to about 2.0; preferably, x is about 0.9 to about 1.8, more preferably about 0.9 to about 1.5. The silicon oxide can include SiO and / or SiO2. Preferably, the silicon oxide includes SiO; more preferably, the silicon oxide is SiO. The silicon oxide particles typically include about 95% or more silicon oxide, preferably about 99% or more silicon oxide, ignoring impurities. Impurities here are defined as elements other than silicon and oxygen. Particles containing one or more silicon oxides often include some elemental silicon.

[0015] The coating of the coated silicon-containing particles is composed of lithium silicate and carbon. The carbon content of the coated particles is about 0.10% by weight or more, preferably about 0.10% by weight to about 10.0% by weight, more preferably about 0.10% by weight to about 8.0% by weight, and even more preferably about 0.10% by weight to about 5% by weight, based on the total weight of the coated particles. In the coating, the carbon is usually amorphous.

[0016] In the coated particles, the lithium is usually in the form of lithium silicate. The lithium silicate in the coating has the formula Li a S b O cwhere a is about 2 to about 8, b is about 1 to about 3, and c is about 3 to about 7. Typically, the lithium silicates formed are Li2SiO3, Li2Si2O5, Li4SiO4, Li8SiO6, Li In some embodiments, the lithium silicate is Li2SiO3, Li2Si2O5, or a mixture thereof.

[0017] The lithium silicates in the coatings usually have some degree of crystallinity, so that a particular lithium silicate can be examined by X-ray powder diffraction (XRD), which is typically identified by these characteristic peaks of the (111) plane. For example, Li2SiO3 is identified by a peak at 2θ=27°, which corresponds to the (111) plane of Li2SiO3. Li2Si2O5 is identified by a peak at 2θ=24.7°, which corresponds to the (111) plane of Li2Si2O5. Li4SiO4 is identified by a peak at 2θ=28.3°, which corresponds to the (111) plane of Li4SiO4.

[0018] The amount of lithium silicate in the coated particles is such that the lithium content of the coated particles is about 1% by weight or more based on the total weight of the coated particles. Typically, the lithium content is about 1% by weight to about 15% by weight, preferably about 1% by weight to about 12.5% ​​by weight, more preferably about 1% by weight to about 10% by weight, even more preferably about 1.5% by weight to about 8% by weight, and even more preferably about 1.5% by weight to about 5% by weight based on the total weight of the coated particles.

[0019] In the coated particles, the relative amount of lithium to carbon is typically from about 2:1 to about 50:1 by weight, preferably from about 3:1 to about 35:1 by weight, more preferably from about 3:1 to about 25:1 by weight, and even more preferably from about 3:1 to about 16:1 by weight.

[0020] In the method of the present invention, a precursor mixture containing a liquid medium, a carbon precursor, and a lithium precursor is mixed together with silicon-containing particles to form a wet mixture, and the wet mixture is heated to form a coating on the silicon-containing particles.

[0021] The silicon-containing particles are composed of either silicon or one or more silicon oxides. The average particle size and preferences of the silicon-containing particles are as described above for the coated particles.

[0022] Usually, silicon-containing particles made of silicon have a surface made of silicon oxide due to the reaction of silicon atoms on the particle surface with oxygen from air.When silicon-containing particles are made of silicon, the silicon particles typically contain about 95% or more silicon, preferably about 99% or more silicon, ignoring impurities.Since silicon particles often contain small amounts of one or more silicon oxides, impurities are defined here as elements other than silicon and oxygen.

[0023] When the silicon-containing particles are composed of one or more silicon oxides, the silicon oxides are represented by the general formula SiO x and x is about 0.75 to about 2.0; preferably, x is about 0.9 to about 1.8, more preferably about 0.9 to about 1.5. The silicon oxide can include SiO and / or SiO2. Preferably, the silicon oxide includes SiO; more preferably, the silicon oxide is SiO. Mixtures of different silicon oxides can be used; the mixture can be composed of different silicon oxides in separate particles, or particles in which different silicon oxides are present in the same particle. The silicon oxide particles typically contain about 95% or more silicon oxide, preferably about 99% or more silicon oxide, ignoring impurities. Impurities are defined here as elements other than silicon and oxygen.

[0024] In the practice of the invention, a mixture of silicon particles and particles of one or more oxides of silicon may be used.

[0025] In the practice of the present invention, the silicon-containing particles typically have a purity of about 95% or greater, preferably about 98% or greater, and more preferably about 99% or greater.

[0026] In the practice of the present invention, the silicon-containing particles may be silicon-containing particles that have been subjected to a surface treatment (e.g., treatment with a surfactant or carbonization).Similarly, the silicon-containing particles may be oxidized silicon-containing particles.

[0027] In some of the methods of the invention for forming a composition comprising silicon-containing particles having a coating thereon consisting of carbon and one or more lithium silicates, wherein the coated silicon-containing particles have a carbon content of about 0.10 wt % or more and a lithium content of about 1 wt % or more based on the total weight of the coated silicon-containing particles, the method includes: a) mixing together the silicon-containing particles with a precursor mixture comprising a liquid medium, a carbon precursor, and a lithium precursor to form a wet mixture; and b) heating at least a portion of the wet mixture to form the coating on the silicon-containing particles.

[0028] In the practice of the present invention, the lithium precursor is often a lithium compound, typically an inorganic or organic lithium salt; lithium metal and lithium alloys can also be used as lithium precursors. Lithium compounds that are not silicon-containing salts can be used as lithium precursors. Any mixture of two or more lithium compounds, or mixtures from different types of lithium sources (e.g., lithium alloys and lithium compounds) can be used as lithium precursors.

[0029] Lithium metal and / or lithium alloys (e.g., containing silicon, magnesium, or aluminum) can be used as lithium precursors, either alone or in combination with one or more of the multiple organic and / or inorganic lithium salts. When lithium metal and / or lithium alloys are used, an inert atmosphere that excludes water and oxygen is usually required; the inert atmosphere is preferably argon, since lithium metal and at least some lithium alloys are known to react with nitrogen. Also, when lithium metal and / or lithium alloys are used, the solvent(s), carbon precursor compound, and any lithium compounds are those that react mildly with or are preferably non-reactive towards lithium metal and / or lithium alloys.

[0030] A mixture of any two or more lithium salts can be used as the lithium precursor; when two or more lithium salts are used, the mixture can include one or more inorganic lithium salts and / or one or more organic lithium salts. Suitable inorganic lithium salts include lithium chloride, lithium bromide, lithium iodide, lithium chlorate, lithium carbonate, lithium bicarbonate, lithium nitrite, lithium nitrate, lithium sulfide, lithium sulfite, lithium sulfate, lithium phosphite, lithium phosphate, and lithium hydroxide. Hydrated forms of these salts can be used, such as lithium hydroxide monohydrate. Suitable organic lithium salts include lithium acetate, lithium acetylacetate, lithium benzoate, lithium citrate, lithium formate, lithium oxalate, lithium salicylate, lithium tartrate, and lithium-containing polymers. Lithium hydroxide is a preferred inorganic lithium salt. When the lithium precursor includes an organic lithium salt and / or a lithium-containing polymer, some of the carbon in the lithium compound can become part of the coating on the silicon-containing particles.

[0031] In the practice of the present invention, a variety of carbon-containing compounds can be used as carbon precursors. The carbon precursor can be dissolved, suspended, dispersed, slurried, or emulsified in the precursor mixture; preferably, the carbon precursor is dissolved or slurried in the precursor mixture, and more preferably, dissolved. A mixture of two or more carbon compounds can be used as the carbon precursor. The compounds that can be used as carbon precursors can be hydrocarbons (containing only carbon and hydrogen) or organic compounds containing one or more heteroatoms, such as oxygen and / or nitrogen. Preferred compounds containing carbon are those that have a higher amount of carbon relative to hydrogen, and thus aromatic compounds are preferred; also polymers such as polyolefins and heteroatom-containing polymers are preferred. In some embodiments, the preferred carbon-containing compounds are dissolved, suspended, dispersed, slurried, or emulsified in the same solvent in which the lithium precursor is present. More preferably, the carbon-containing compounds are dissolved or slurried in the same solvent in which the lithium precursor is present.

[0032] Carbon-containing compounds suitable in the practice of the present invention include pentane, hexane, 2-methylhexane, cyclopentane, cyclohexane, methylcyclohexane, heptane, 4-methylheptane, octane, cyclooctane, nonane, decane, benzene, toluene, xylene, ethylbenzene, amylbenzene, methylethylbenzene, diethylbenzene, mesitylene, 1,2,4-triethylbenzene, 1,3,5-triethylbenzene, amylbenzene, tetrahydronaphthalene, refined heavy oil, pitch, polyethylene, polypropylene, polyacrylic acid, polymaleic acid, polyfumaric acid, polycrotonic acid, poly(pentene) acid, polymethacrylic acid, polydimethacrylic acid, poly(allyl alcohol), poly(n-propyl)acrylate, poly(hydroxymethyl ... Examples of suitable carbon-containing polymers include acrylate, poly(2-hydroxyethyl)acrylate, poly(2-carboxyethyl)acrylate, poly(3-ethoxy-3-oxopropyl)acrylate, poly(methylcarbamylethyl)acrylate, poly(2-hydroxyethyl)methacrylate, polyvinylpyrrolidone (PVP), polyacrylamide, polymethacrylamide, poly(N-isopropyl)acrylamide, polyvinylacetamide, polyvinyl alcohol, polyvinyl-N-methylacetamide, poly(N-hydroxymethyl)acrylamide, poly(N-hydroxyethyl)acrylamide, poly(N-methoxymethyl)acrylamide, poly(N-ethoxymethyl)acrylamide, polyacrylonitrile, sucrose, and natural polymers such as cellulose and polysaccharides. Polyacrylic acid and polyacrylonitrile are preferred compounds containing carbon because they are soluble in polar solvents such as water.

[0033] The amount of lithium precursor relative to the silicon oxide particles is such that the atomic ratio of lithium:silicon is preferably at least about 0.03:1, or in the range of about 0.03:1 to about 1:1, more preferably about 0.03:1 to about 0.5:1, and more preferably about 0.03:1 to about 0.4:1.

[0034] The amount of carbon precursor relative to the silicon oxide particles is such that the atomic ratio of carbon:silicon is about 0.01:1 or more, preferably about 0.015:1 or more, or in the range of about 0.01:1 to about 4:1, preferably about 0.02:1 to about 3:1, more preferably about 0.02:1 to about 0.2:1. These amounts are selected assuming that the carbon yield of the coated particles is about 20%, where the carbon yield is the amount of carbon on the particles relative to the amount of carbon provided by the carbon precursor. For example, if the carbon precursor provides 100 grams of carbon, then a 20% carbon yield is 20 grams of carbon.

[0035] The amount of lithium precursor relative to the carbon precursor is such that the atomic ratio of lithium:carbon is about 0.0015:1 or greater, preferably about 0.015:1 or greater, or in the range of about 0.0015:1 to about 100:1, preferably in the range of about 0.015:1 to about 75:1, and more preferably in the range of about 0.03:1 to about 50:1.

[0036] The liquid medium may be any of a variety of solvents or a mixture of two or more solvents, so long as the lithium precursor and the carbon precursor are dissolved, suspended, dispersed, slurried, or emulsified in the liquid medium. Preferably, the lithium precursor and the carbon precursor are The lithium precursor and the carbon precursor may be in different states in the liquid medium; for example, the lithium precursor may be dissolved in the liquid medium while the carbon precursor is suspended in the liquid medium. In some embodiments, the lithium precursor is in one or more solvents, whether dissolved, suspended, dispersed, slurried, or emulsified, and the carbon precursor is in another one or more solvents, whether dissolved, suspended, dispersed, slurried, or emulsified, and the lithium precursor in the solvent(s) is mixed with the carbon precursor in the solvent(s) to form a wet mixture. In preferred embodiments, polar solvents are preferred since the lithium precursor typically has at least some ionic character. In some cases, the carbon precursor may have limited solubility in a polar solvent, which can be dissolved in a non-polar solvent to form a carbon precursor solution, which is then mixed with a solution of the lithium precursor to obtain a liquid medium containing the carbon precursor and the lithium precursor. If the carbon precursor is dissolved in a non-polar solvent, the non-polar solvent preferably has some miscibility with the polar solvent in which the lithium precursor is dissolved. Precursor mixtures in which the lithium precursor and / or carbon precursor are suspended, partially dissolved, slurried, emulsified, or dispersed may result in less uniform coatings formed from such precursor mixtures, however such precursor mixtures may offer other advantages such as ease of transfer.

[0037] The polar solvent may be protic or aprotic. Mixtures of polar solvents may be used, such as mixtures containing aprotic and protic solvents. Suitable polar solvents that may be used in the practice of the present invention include water, alcohols, esters, ketones, nitriles, and halogenated hydrocarbons. Suitable polar solvents include water, methanol, ethanol, n-propanol, 2-propanol, 1-butanol, 2-methyl-1-propanol, 1-methyl-1-propanol, cyclopropylmethanol, cyclobutanol, cyclopentanol, acetonitrile, propionitrile, hexanenitrile, benzonitrile, acetone, methyl ethyl ketone, pentanone, hexanone, heptanone, tetrahydrofuran, diethyl ether, di-n-propyl ether, diisopropyl ether, di-n-butyl ether, butyl ethyl ether, cyclohexyl methyl ether. , tetrahydrofuran, tetrahydropyran, 1,3-dioxane, 1,4-dioxane, 1,3-dioxolane, ethylene glycol, diethylene glycol, ethyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, amyl acetate, hexyl acetate, methyl propionate, ethyl propionate, ethyl butyrate, ethyl benzoate, dichloromethane, dibromomethane, dibromoethane, trichloromethane, tribromomethane, 1,2-dichloroethane, chlorobenzene, bromobenzene, dimethylformamide, dimethylsulfoxide, and N-methylpyrrolidinone. Preferably, the polar solvent is a protic solvent; more preferably, the polar solvent is water or an alcohol, such as ethanol or isopropyl alcohol. Water is the preferred polar solvent.

[0038] Non-polar solvents include liquid aromatic hydrocarbons and liquid aliphatic hydrocarbons. Liquid hydrocarbons suitable for the practice of the present invention include pentane, hexane, 2-methylhexane, cyclopentane, cyclohexane, methylcyclohexane, heptane, 4-methylheptane, octane, cyclooctane, nonane, decane, benzene, toluene, xylene(s), ethylbenzene, mesitylene, methylethylbenzene, diethylbenzene, cumene, cymene, and tetrahydronaphthalene.

[0039] When the liquid medium includes one or more carbon-containing solvents, a portion of the carbon in the carbon-containing solvent(s) can become part of the coating on the silicon-containing particles.

[0040] Typically, the amount of liquid medium in the (wet) mixture formed from the precursor mixture and the silicon-containing particles is sufficient to form a paste or a paste-like mixture. If the amount of liquid medium is more than enough to form a paste or paste-like mixture, the mixture and the coating formed therefrom may be more uneven. If the amount of liquid medium is more than enough to form a paste or paste-like mixture, the excess liquid medium can be removed. If the liquid medium from the precursor mixture is not enough to form a paste after mixing the precursor mixture with the silicon-containing particles, more solvent can be added.

[0041] The amount of liquid medium required to wet the silicon-containing particles varies depending on the viscosity of the liquid medium and the particle size of the silicon-containing particles. The liquid medium is preferably in an amount of about 0.2 mL or more per gram of one or more silicon oxide particles. In terms of range, the liquid medium is preferably about 0.2 mL to about 2 mL per gram of silicon-containing particles, more preferably about 0.3 mL to about 1 mL per gram of silicon-containing particles, even more preferably about 0.4 mL to about 1 mL per gram of silicon-containing particles, and even more preferably about 0.4 mL to about 0.75 mL per gram of silicon-containing particles.

[0042] The concentration of the lithium precursor in the liquid medium can be any convenient concentration; preferably, the concentration is selected such that the lithium precursor is slurried or dissolved, more preferably dissolved, in the liquid medium. Very low concentrations, for example less than about 1 wt%, are undesirable as less lithium will become part of the coating. Typical concentrations of the lithium precursor in the liquid medium are about 2 wt% or more, or in the range of about 2 wt% to about 50 wt%, preferably about 2 wt% to about 35 wt%.

[0043] The concentration of the carbon precursor in the liquid medium can be any convenient concentration; preferably, the concentration is selected so that the carbon precursor is slurried or dissolved, more preferably dissolved, in the liquid medium. Very low concentrations, for example less than about 1 wt%, are undesirable because less carbon will become part of the coating. For oligomers and polymers, typical concentrations of the carbon precursor in the liquid medium range from about 3 wt% or more, or from about 3 wt% to about 20 wt%, preferably from about 3 wt% to about 15 wt%, more preferably from about 3 wt% to about 12 wt%, and even more preferably from about 3 wt% to about 10 wt%. It has been found that the viscosity of the solution is a better variable for obtaining a good carbon-containing coating than the concentration of the carbon precursor in the liquid medium. The concentration of the oligomer and polymer provides a solution of the desired viscosity. If the carbon precursor is not an oligomer or polymer, the concentration of the carbon precursor in the liquid medium is usually much higher than the oligomer and polymer to achieve a similar viscosity. The preferred viscosity of the liquid medium containing the lithium precursor and the carbon precursor is approximately equal to the viscosity of a liquid medium containing 8 weight percent lithium hydroxide and 12 weight percent poly(acrylic acid).

[0044] In the step of mixing together, the precursor mixture is often added to the silicon-containing particles. Other methods of combining the silicon-containing particles and the precursor mixture together may be used, such as placing both in a container at the same time or adding the silicon-containing particles to the precursor mixture.

[0045] For mixing, the silicon-containing particles and the precursor mixture are mixed together until the silicon-containing particles are wetted to form a wet mixture. In a preferred embodiment, the wet mixture has a paste-like consistency. Mixing can be performed by any convenient means, such as a magnetic stirrer, an overhead stirrer, or a shaker. The mixing step is typically a few minutes in duration on a laboratory scale.

[0046] In the heating step, the wet mixture is typically held at the desired temperature(s) for about 1 to about 6 hours on a laboratory scale. Shorter heating times may be sufficient for some reagent combinations, while longer heating times may be required for other reagent combinations.

[0047] The temperature in the heating step is usually about 500° C. or higher, more preferably about 600° C. or higher, even more preferably about 700° C. or higher, and even more preferably about 800° C. or higher. In terms of range, the temperature in the heating step is in the range of about 500° C. to about 1100° C., preferably in the range of about 550° C. to about 1100° C., more preferably in the range of about 600° C. to about 1000° C., and even more preferably in the range of about 600° C. to about 950° C. Under these conditions, silicon carbide is not formed.

[0048] It has been observed that the amount of lithium compound in the mixture and the temperature during the heating step affect the formation of lithium silicate.

[0049] One advantage of the present invention is that the heating step does not usually need to be performed under an inert atmosphere. However, it is preferred to perform the heating step under an inert atmosphere. The inert atmosphere may be static or a flow of inert gas(es). As used throughout this specification, "inert atmosphere" refers to a gas or gas mixture that is essentially oxygen-free, although incidental amounts of oxygen may be present in the inert atmosphere. In the practice of the present invention, water may be present in the inert atmosphere unless lithium metal and / or lithium alloys are used. The inert atmosphere is usually argon, nitrogen, helium; mixtures of two or more inert gases may be used; nitrogen and argon are preferred. When the lithium precursor includes lithium metal and / or one or more lithium alloys, the inert gas is preferably argon.

[0050] In some methods of the invention, a portion of the carbon precursor can be introduced into the wet mixture instead of a portion of the wet mixture, preferably during heating of the wet mixture, by feeding it thereto. This portion of the carbon precursor is preferably fed into the wet mixture in liquid or gas form, more preferably in gas form. The gaseous form of the carbon precursor can be a carbon precursor in the gas phase at ambient conditions, and / or the gaseous carbon precursor can be obtained by heating and / or by passing an inert gas over the surface of the carbon precursor.

[0051] Another method of the present invention for forming a composition comprising silicon-containing particles having a coating thereon, the coating being made of carbon and one or more lithium silicates, comprises: A) mixing together silicon-containing particles with a precursor mixture comprising a liquid medium and a lithium precursor to form a wet mixture; and B) heating at least a portion of the wet mixture while providing a carbon precursor to the wet mixture to form a coating on the silicon-containing particles. The coated silicon-containing particles have a carbon content of about 0.10 wt.% or more and a lithium content of about 1 wt.% or more, based on the total weight of the coated silicon-containing particles. In these methods, the silicon-containing particles, the liquid medium, the lithium precursor, the carbon precursor, the relative amounts of these materials, the heating conditions, and all of the preferences thereof are as described above.

[0052] In those methods of the invention where the carbon precursor is introduced by feeding it to the wet mixture, the carbon precursor is preferably fed to the wet mixture in liquid or gaseous form, more preferably in gaseous form. The gaseous form of the carbon precursor can be a carbon precursor in the gas phase at ambient conditions and / or the gaseous carbon precursor can be obtained by heating and / or by passing an inert gas over the surface of the carbon precursor.

[0053] In the methods of the present invention where the carbon precursor is introduced by feeding it to the wet mixture, at least a portion of the carbon precursor is preferably in the gas phase. In these embodiments, at least a portion of the carbon precursor can be a gas phase compound. Suitable gas phase carbon precursors include carbon dioxide, ethylene, acetylene, propylene, ethane, propane, cyclopropane, methylcyclopropane, butane, cyclobutane, and dimethyl ether.

[0054] Optionally, after the heating step of the method of the invention, and preferably after cooling, the coated particles can be contacted with and / or washed with one or more solvents to remove unreacted lithium precursor and / or unreacted carbon precursor, as well as to remove undesired by-products. The solvent for contacting and / or washing can be the same or different from the solvent that formed the liquid medium during the process.

[0055] The coated silicon-containing particles formed by the method of the present invention have a carbon content of about 0.10 wt.% or more and a lithium content of about 1 wt.% or more based on the total weight of the coated particles. The average particle size, carbon content, lithium content, lithium silicate, and the relative amount of lithium to carbon, and their preferences, are as described above for the composition of the present invention.

[0056] The coated silicon-containing particles of the present invention can be used as an anode (negative electrode) active material. In some embodiments, the coated silicon-containing particles are coated on a current collector, optionally in the form of a slurry containing the coated silicon-containing particles. At least a portion of the coated current collector becomes at least a portion of the anode. The anode containing the coated silicon-containing particles of the present invention as an active material can be used in secondary batteries, particularly lithium secondary batteries. Secondary batteries are typically composed of an anode, a cathode, a separator, and an electrolyte solution.

[0057] The following examples are offered for illustrative purposes and are not intended to impose limitations on the scope of the invention.

[0058] In the examples, the lithium silicate present was determined by X-ray powder diffraction (XRD). X-ray powder diffraction analysis was performed on a D8 ADVANCE powder diffractometer (Bruker Inc.) using a CuKα anode (λ=1.54060 Å) as the X-ray source. The X-ray powder diffraction patterns of the inventive materials (coated silicon-containing particles) in all the following examples showed no peak at 2θ=35.8±0.2°. The peak at 2θ=35.8±0.2° corresponds to silicon carbide. It was concluded that silicon carbide is not formed in the inventive materials.

[0059] Total carbon content (TC), lithium content (ICP), and surface area (N2 isothermal adsorption, also called Braun-Emmet-Teller or BET analysis) were also measured. EXAMPLES

[0060] Example 1 A solution containing lithium hydroxide (12.3 wt%) and poly(acrylic acid) (6 wt%, PAA) was prepared by dissolving lithium hydroxide monohydrate (LiOH·HO) and PAA in water. Silicon monoxide (4.0 g, SiO) with an average particle size of 5 μm was weighed into a beaker. The LiOH and PAA solution was added dropwise to the SiO in the beaker while stirring until all SiO particles appeared wet. A total of 2.62 g of LiOH+PAA solution was used. This corresponds to 0.322 g LiOH and 0.157 g PAA.

[0061] The wet mixture was transferred into a stainless steel reactor and then heated to 700°C under flowing argon gas and held at 700°C for 3 hours. After the reactor was cooled to room temperature, the treated material (coated silicon-containing particles) was removed from the reactor and analyzed. Three more experiments were performed with this method, varying the amount, concentration, and temperature. Amounts, concentrations, and temperatures are summarized in Table 1A.

[0062] In the XRD patterns in Figure 1, the x-axis is 2θ (combined 2θ / θ) and the y-axis is counts. The XRD pattern for experiment A in Figure 1 has a peak at 2θ = 27° corresponding to the (111) plane of Li2SiO3, indicating the presence of Li2SiO3 in the processed material. The peaks in Figure 1 marked with solid diamonds are for Li2SiO3. Particle characteristics for all experiments are summarized in Table 1B. The weight percentage values ​​reported in Table 1B are relative to the total weight of the coated particles. [Table 1A] [Table 1B]

[0063] The comparison between the calculated and experimentally measured Li contents is very close, suggesting that little or no lithium is lost in the preparation process.

[0064] Example 2 Another preparation of coated silicon-containing particles was carried out as described in Example 1. The reagents, amounts, and conditions are summarized in Table 2A. A portion of the product obtained in Run I was cooled to room temperature, then heated to 900°C, held at 900°C for 1 hour, and then cooled to room temperature to form the product of Run II. In Run IV, a stream of argon was blown through the cyclohexane while the reactor was heated to 900°C, and a total of 30 mL (23.1 g) of cyclohexane was charged into the reactor.

[0065] In the XRD pattern of Experiment II in FIG. 2, the x-axis is 2θ (combined 2θ / θ) and the y-axis is counts. The XRD pattern of Experiment II in FIG. 2 has a peak at 2θ=27° corresponding to the (111) plane of Li2SiO3, a peak at 2θ=24.7° corresponding to the (111) plane of Li2Si2O5, and a peak at 2θ=33.1° corresponding to the (111) plane of Si, indicating that the treated material contains Li2SiO3, Li2Si2O5, and Si. The particle characteristics for all experiments are summarized in Table 2B below. The weight percentage values ​​reported in Table 2B are relative to the total weight of the coated particles. [Table 2A] [Table 2B]

[0066] After cross-section polishing (CP), a portion of the coated silicon-containing particle from experiment III was examined by energy dispersive X-ray analysis (EDX), which showed that the coating contained the elements Si, O, and C.

[0067] Example 3 Portions (1.0 g) of the coated silicon-containing particles from several of the runs in the above examples were each made into a slurry containing the following components: 5% by weight of coated silicon-containing particles; 89% by weight graphite; 1.5% by weight carboxymethylcellulose (CMC); 3% by weight styrene-butadiene rubber (SBR); 1.5% by weight of carbon black; and water. The amount of water was such that the solids content of the slurry was about 60% by weight. The slurry was coated onto a copper foil current collector, and the coating was then dried and then calendared to a porosity of 30% to form an electrode containing the coated silicon-containing particles. The loading of the coated silicon-containing particles on the electrode was about 8 mg / cm. 2 Five coin cells were assembled from each calendered electrode using lithium foil as the counter electrode and LiPF6 (1M) in ethylene carbonate / ethyl methyl carbonate (30:70 wt / wt) as the electrolyte solution. The cells were cycled 10 times at C / 20. For comparison, both pristine SiO2 without any treatment and graphite anode without SiO2 were also tested under the same conditions. The first cycle capacity and coulombic efficiency are summarized in Table 3 below. [Table 3]

[0068] A component referred to by a chemical name or formula anywhere in this specification or the claims thereto, whether in the singular or plural form, is recognized as being present prior to contact with another substance (e.g., another component, solvent, etc.) referred to by the chemical name or chemical species. It is immaterial what chemical changes, transformations, and / or reactions, if any, occur in the resulting mixture or solution, as such changes, transformations, and / or reactions are the natural result of bringing together the particular components under the conditions required in accordance with this disclosure. Thus, the components are recognized as components that are brought together in connection with carrying out a desired operation or in forming a desired composition. Also, in the claims that follow, although a reference may be made to a substance, component, and / or ingredient in the present tense ("comprises," "is," etc.), the reference refers to the substance, component, and / or ingredient that was present immediately prior to being first contacted, blended, or mixed with one or more other substances, components, and / or ingredients in accordance with this disclosure. Thus, it is understood that the substance, component, and / or ingredient is present prior to being contacted, blended, or mixed with the one or more other substances, components, and / or ingredients in accordance with this disclosure. The fact that the original identity may be lost during the process through chemical reactions or transformations is not a practical concern when performed according to the ordinary skill of a chemist in accordance with the present disclosure.

[0069] The present invention may comprise, consist of, or consist essentially of the materials and / or procedures described herein.

[0070] As used herein, the term "about" to modify the amount of an ingredient in a composition or employed in a method of the present invention refers to variations in numerical quantities that may occur, for example, due to typical measuring and liquid handling procedures used to make concentrates or use solutions in the real world; due to inadvertent errors in these procedures; due to differences in the manufacture, source, or purity of ingredients used to make the composition or carry out the method; etc. The term "about" also encompasses amounts that differ due to different equilibrium conditions of the composition resulting from a particular initial mixture. The claims include equivalents to amounts whether or not modified by the term "about."

[0071] Unless expressly indicated otherwise, the article "a" or "an" as used herein is not intended, and should not be construed as, limiting the specification or claims to the single element to which the article refers. Rather, the article "a" or "an" as used herein is intended to cover one or more such elements, unless the context expressly dictates otherwise.

[0072] This invention is susceptible to considerable variation in its practice, and therefore the foregoing description is not intended to limit, and should not be construed as limiting, the invention to the specific exemplifications presented hereinabove.

Claims

1. 1. A composition comprising coated silicon-containing particles having a coating consisting of carbon and one or more lithium silicates, said coated silicon-containing particles having a carbon content of 0.44% to 10% by weight and a lithium content of 1% to 15% by weight based on the total weight of said coated silicon-containing particles.

2. 2. The composition of claim 1, wherein the lithium and carbon are in a lithium:carbon ratio of from 2:1 to 50:1 by weight.

3. An anode having an active material comprising the composition of any one of claims 1-2.

4. An anode having an active material comprising the composition according to any one of claims 1 to 2. Cathode, Separator, and electrolyte solution A secondary battery including:

5. a) mixing together silicon-containing particles with a precursor mixture comprising a liquid medium, a carbon precursor, and a lithium precursor to form a wet mixture; and b) heating at least a portion of the wet mixture to form a coating on the silicon-containing particles, wherein the heating is at a temperature of 500° C. or greater; 1. A method for forming a coating of carbon and one or more lithium silicates on silicon-containing particles, comprising: After forming the coating, a coated silicon-containing particle is obtained, the coated silicon-containing particle having a carbon content of 0.44 wt % to 10 wt % and a lithium content of 1 wt % to 15 wt %, based on the total weight of the coated silicon-containing particle.

6. The method of claim 5 further comprising providing at least a portion of a carbon precursor to the wet mixture during heating of the wet mixture.

7. A) mixing together silicon-containing particles with a precursor mixture comprising a liquid medium and a lithium precursor to form a wet mixture; and B) heating at least a portion of the wet mixture while delivering a carbon precursor to the wet mixture to form a coating on the silicon-containing particles, wherein the heating is at a temperature of 500° C. or greater; 1. A method for forming a coating of carbon and one or more lithium silicates on silicon-containing particles, comprising: After forming the coating, a coated silicon-containing particle is obtained, the coated silicon-containing particle having a carbon content of 0.44 wt % to 10 wt % and a lithium content of 1 wt % to 15 wt %, based on the total weight of the coated silicon-containing particle.

8. 8. The method of claim 6 or 7, wherein the carbon precursor is supplied to the wet mixture in gaseous form.

9. 8. The method of claim 5 or 7, wherein the liquid medium comprises a polar solvent or a mixture of a polar solvent and a non-polar solvent.

10. The method according to any one of claims 5 to 8, wherein the carbon precursor is an organic compound comprising carbon and hydrogen, and optionally oxygen and / or nitrogen.

11. 8. The method of claim 5 or 7, wherein the carbon precursor is in an amount relative to silicon oxide particles to provide an atomic ratio of carbon:silicon of 0.01:1 or greater.

12. 8. The method of any one of claims 5 to 7, wherein the lithium precursor is in an amount relative to the carbon precursor to provide an atomic ratio of lithium:carbon of 0.0015:1 or greater.

13. 8. The method of claim 5 or 7, wherein the lithium precursor is in an amount relative to silicon oxide particles to provide an atomic ratio of lithium:silicon of 0.03:1 or greater.

14. The method of claim 5 , wherein the carbon precursor has a concentration of 3% by weight or greater in the liquid medium.

15. 8. The method of claim 5 or 7, wherein the lithium precursor has a concentration of 2% by weight or more in the liquid medium.

16. 8. The method of claim 5 or 7, wherein the liquid medium is in an amount of 0.2 mL or more per gram of the silicon-containing particles.

17. The method of any one of claims 5 to 16, wherein the heating is carried out in an inert atmosphere.

18. 6. The method of claim 5, further comprising combining a solution of the carbon precursor with a solution of the lithium precursor to obtain the liquid medium containing the carbon precursor and the lithium precursor.

19. The method of any one of claims 5 to 7, further comprising forming at least a portion of an anode from an active material comprising the coated silicon-containing particles.

20. 20. The method of claim 19, further comprising forming a secondary battery from: an anode having an active material comprising the coated silicon-containing particles; a cathode; a separator; and an electrolyte solution.

Citation Information

Patent Citations

  • Negative electrode active material for non-aqueous electrolyte rechargeable battery, and non-aqueous electrolyte rechargeable battery using negative electrode active material

    CN104603993A

  • Graphene / solid-state electrolyte composite coated silicon composite negative electrode and preparation method thereof

    CN107579239A

  • Space buffer lithium-doped silicon oxide composite material, preparation method of composite material and lithium ion battery

    CN108232145A

  • Negative electrode material for nonaqueous secondary battery and method for producing the material, and lithium ion secondary battery

    JP2011222151A

  • Composite particle for nonaqueous electrolyte secondary battery

    JP2014220216A